Radiation Effects On Mammalian DNA - PAC Method And Theory - Tsoulou, E. P.; Kalfas, C. A. (HNPS Advances in Nuclear Physics, 2019)
The flexibility of DNA and its molecular dynamics have been the subject of various studies. One of the techniques that have been employed is the PAC method, which is considered as a valuable tool for such studies. In PAC experiments we can detect the angular correlation of two γ rays emitted in succession by a radioactive probe. Using the hyperfine interaction of the probe with it's surrounding electric field gradient we can obtain information about the dynamics of the molecules to which the probe is attached. In this work, for the PAC measurements, we use m I n which is added in a buffered solution of calf thymus DNA, exposed to various doses (0- 80 Gy) of 7-rays.